2012
DOI: 10.1100/2012/941259
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 Expression in Immunohistochemistry Has No Prognostic Significance in Gastric Cancer Patients

Abstract: The role of HER-2 expression as a prognostic factor in gastric cancer (GC) is still controversial. The aim of the study was to asses HER-2 status, its correlations with clinicopathological parameters, and prognostic impact in GC patients. Tumor samples were collected from 78 patients who had undergone curative surgery. In order to evaluate the intensity of immunohistochemical (IHC) reactions two scales were applied: the immunoreactive score according to Remmele modified by the authors and standardised Hercep t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…In the case of HER-2, some previous studies have reported that amplification of the HER2 gene or overexpression of its encoded protein in gastric cancer is associated with significantly shortened disease-free survival and overall survival [9,25,27]. However, recent studies have shown no significant prognostic value of HER2 in gastric cancer [36,37]. Recurrence pattern between loco-regional recurrence and distant recurrence was not related to alterations in EGFR and HER-2 (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…In the case of HER-2, some previous studies have reported that amplification of the HER2 gene or overexpression of its encoded protein in gastric cancer is associated with significantly shortened disease-free survival and overall survival [9,25,27]. However, recent studies have shown no significant prognostic value of HER2 in gastric cancer [36,37]. Recurrence pattern between loco-regional recurrence and distant recurrence was not related to alterations in EGFR and HER-2 (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…However, the prognostic role of Her-2/neu in gastric cancer is still controversial. Some studies have shown no predictive value with survival, and some have shown a correlation between Her-2/neu and worse outcome [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Her-2 gene amplification has been reported in various types of cancer, including ovarian, lung and breast cancers (13,14,25). It has been reported that Her-2 is overexpressed in 9-38% of patients with gastric cancer (26), and is associated with certain clinicopathological characteristics and a poor survival in univariate analysis, but is not independently correlated with prognosis in multivariate analysis (27,28). However, in the studies by Okada et al (6) and Li et al (29), positive FoxM1 expression was an independent prognostic factor in gastric cancer, but did not correlate with any clinicopathological characteristics; the opposite occurred for Her-2.…”
Section: Discussionmentioning
confidence: 99%